Think Tanks: quem são, como atuam e qual seu panorama de ação no Brasil - Juliana Cristina Rosa Hauck (2015)
Among the universe of actors that seek to retain States attention trough the dissemination of public policy ideas think tanks reveal themselves as a kind of actor whose field of study is underexplored, globally and especially in Brazil. So, the dissertation focused on that matter trying to comprehend who they are, how they act and which is the panorama they face in Brazil. Facing a limited field of discussion, starting from the thin tank definition, the study was dedicated, in the first moment, to work on a discussion regarding this concept. We offered, in that matter, a critical analysis about the controversies associated to the concept as it has been used and pointed alternatives to glimpse a more flexible comprehension of the category, mobilizing a definition. This definition was used as an axis of conduction to all analytic outlines in the study facing a fragile theoretical outline present by the literature. From that, the study was dedicated to clarifying comprehensively the context of institutional construction of Brazil in the XX century, approaching aspects of the cultural-historical, political, social-economical perspective, through the prism of the Brazilian political grammar. This views permitted us identify in what measures this trajectory favored or not the foundation of think tanks in the country, as well as stablished the bases to indications about the ways in which this context molded them, causing hybridizations particular to Brazil. These can provide the phenomena very particular features. There was also an effort in identifying, through the analysis of wider contextual environments in contemporary times, which perspectives reveal themselves to these organizations in actual time. Without disregard of the core of the definition transversally adopted in the study, we identified several indicators to growth and consolidation of these organizations. Lastly, we sought to understand the phenomena through the analysis of some organizations in Brazil that we were able to classify, by the concept mobilized, as think tanks. This investigation permitted not only the test about the operationalization of the concept but also allowed ponderations regarding the organizational, typological and ideas marketing profile of Brazilian TTs. This description provided us a more concrete overlook towards the phenomena in Brazil, opening perspectives to base and enrich more profound discussions in a vast research agenda still opened about the theme.